The Influence of Knowledge and Physical Activity on the Nutritional Status of Adolescents - Sholihah, Nur Arifatus; Pellondou, Kurnia Bend. Yunita; Bakker, Camelia (Indonesian Journal of Global Health Research, 2023)
Adolescence is a period where a person experiences a transition period in his life as preparation for adulthood. During this period, adolescents experience a change from child behavior to adult behavior. Judging from the changes, teenagers are experiencing physiological and psychological transitions. Adolescence is a time when many problems can arise, including nutritional needs. Nutritional problems among teenagers that are still common in Indonesia include anemia, stunting (a condition where children stop growing as they get older), wastismang (thin), and obesity (fat). The aim of the research carried out was to determine the effect of knowledge of nutritional action materials on adolescents. The type of research used is descriptive research with a cross sectional approach. The sample in this study was 30 Almuhajirin High School students. The variables studied were knowledge about nutrition and physical activity. Data processing was analyzed descriptively. The influence of knowledge and physical activity on nutritional status using the Chi Square method. The results of the research conducted showed that the pre-test was 47% and the post-test was 56.9%, indicating that there was an influence of advice to expand knowledge as an effort to improve adolescent nutrition. It can be concluded that the higher the level of knowledge about nutrition and physical activity of students, the better their nutritional status will be.